Search for an effective morphometric parameter corresponding to the highly vacuolated stage of microspores in common barley - Ya. A. Blinova; D. D. Babina; A. S. Khanova; M. Yu. Korol; E. V. Bondarenko (Зерновое хозяйство России, 2023)
Common barley (Hordeum vulgare L.) is an important agricultural crop, when the applied biotechnology methods are used for the development of new varieties. One of the promising biotechnological approaches is the production of haploid plants from anther culture or isolated microspores. The efficiency of these androclinium-based methods depends on the developmental phase of microspores in the anthers. For cereals, the optimal stage of development is a mononuclear, highly vacuolated microspore.   Considering the labor intensity of cytological control of the stages of formation of haploid germ cells for routine biotechnological procedures, a reliable and simple method for selecting ears with microspores at the optimal stage of development is required. In this regard, the purpose of the current study was to identify an effective morphometric parameter corresponding to the highly vacuolated mononuclear stage of microspores in the anthers of common barley of domestic varieties ‘Leon’, ‘Fox 1’ and ‘Ratnik’ and the reference variety for genetic transformation ‘Golden Promise’, for the introduction of these varieties into in vitro culture.   In all studied genotypes, there has been found polymorphism of microspores, due to the asynchrony of their development. The largest number of highly vacuolated microspores was established for the domestic variety ‘Leon’. In the search for a morphometric parameter associated with the optimal stage of microspores, there have been analyzed such indicators as the interval distance between the flag leaf and the second one (F-2l), the interval distance between the flag leaf and the tip of the ear located in the tube (F-K), the length and width of the ear, and also calculated the morphometric criterion (ratio of F-2l:F-K), previously proposed to determine the optimal stage of anther development in a number of genotypes of spring bread wheat. There has been established that, of all the parameters studied, the stage of development of microspores as initial androclinium cells can be determined using a morphometric criterion. However, it is important to remember that, in addition to the intravarietal asynchrony of microspore formation, there is high intervarietal variability, therefore, the values of the morphometric criterion should be selected for each variety introduced into the biotechnological process.